The Value of Faith in the Book Ya Allah I'm Home by Alfialghazi and Its Relevance To Adolescent Character Education - Rahmawati, Putri; Mujahidun, M; Hidayati, Istania Widayati (Prosiding University Research Colloquium, 2023)
The phenomenon of moral, character and moral decline in adolescents is one of the problems in society as one of the negative impacts of the entry of the era of globalization and modernization. Therefore, in the current era of globalization, teenagers should have a strong faith, in order to avoid acts that deviate from the teachings of Islam. Within the scope of education, literary works can act as a means of learning so that benefits and lessons can be taken in life. Through literary works, the author can share the values of faith with teenagers without having to patronize, besides that the content in the book can become an exemplary preaching for teenagers. The aims of this study were: (1) To find out the values of the faith contained in the book Ya Allah Aku Pulang by Alfialghazi (2) To find out the relevance of the values of the faith in the book Ya Allah Aku Pulang by Alfialghazi to the character education of youth. This research is a library research using qualitative research methods. This research is descriptive with content analysis (Content Analysis). The results of this study indicate that: First, the values of the Aqidah contained in the book Ya Allah I'm Going Home include: Faith in Allah, Faith in Angels, Faith in Allah's Books, Faith in the Messenger of Allah, Faith in the Last Day, and Faith in Qadha' and Qadar. Second, the results of this study also found 2 methods contained in the book Ya Allah I'm Home which includes: (1) Exemplary Method (2) Habituation Method.